The Ubiquitin Ligase Praja1 Reduces NRAGE Expression and Inhibits Neuronal Differentiation of PC12 Cells - Teuber, Jan (Public Library of Science, 2013)
Evidence suggests that regulated ubiquitination of proteins plays a critical role in the development and plasticity of the central nervous system. We have previously identified the ubiquitin ligase Praja1 as a gene product induced during fear memory consolidation. However, the neuronal function of this enzyme still needs to be clarified. Here, we investigate its involvement in the nerve growth factor (NGF)-induced differentiation of rat pheochromocytoma (PC12) cells. Praja1 co-localizes with cytoskeleton components and the neurotrophin receptor interacting MAGE homologue (NRAGE). We observed an enhanced expression of Praja1 after 3 days of NGF treatment and a suppression of neurite formation upon Praja1 overexpression in stably transfected PC12 cell lines, which was associated with a proteasome-dependent reduction of NRAGE levels. Our data suggest that Praja1, through ubiquitination and degradation of NRAGE, inhibits neuronal differentiation. The two murine isoforms, Praja1.1 and Praja1.2, appear to be functionally homologous in this respect.